TECHNO-ECONOMICS OF SEAWEED FARMING ALONG THE COASTS OF KELANTAN, EAST COAST PENINSULAR MALAYSIA - Phang, Siew-Moi; Yeong, Hui-Yin; Hussin, Hanafi; Lim, Phaik-Eem; You, Hack-Churl; You, Hack-Churl; Juan, Joon-Ching (Malaysian Journal of Science, 2017)
A Grand Challenge programme was initiated at the University of Malaya under the Equitable Society Research Cluster, to introduce seaweed farming to the coastal communities at Bachok district, Kelantan. Cultivation trials of selected commercial seaweeds like Kappaphycus (source of carrageenan), Gracilaria (source of agar), Gelidium (source of agar and pulp) and Ulva (salad) will be conducted using on-shore and off-shore systems, and the data collected is used for the techno-economics analysis. This paper discusses the techno-economics of various cultivation systems, as well as the importance of community empowerment, as a guide to the formulation of a roadmap for the integration of seaweed farming into the Bachok coastal communities. Abstrak Satu Program Grand Challenge telah dimulakan dibawah Kluster Penyelidikan Equitable Society di Universiti Malaya bagi memperkenalkan pengkulturan rumpair laut kepada komuniti persisiran pantai di daerah Bachok, Kelantan. Percubaan pengkulturan rumpair laut terpilih seperti Kappaphycus (sumber carrageenan), Gracilaria (sumber agar), Gelidium (sumber agar dan pulpa) dan Ulva (salad) akan dilaksanakan dengan menggunakan sistem tepi pantai (on-shore) dan luar pantai (off-shore), dan data-data yang dikumpulkan ini digunakan dalam analisis tekno-ekonomi. Makalah ini membincangkan tekno-ekonomi bagi pelbagai sistem pengkulturan serta kepentingan pemberdayaan komuniti, sebagai panduan kepada perumusan pelan hala tuju untuk mengintegrasikan pengkulturan rumpair laut ke komuniti pesisiran pantai Bachok. Keywords: seaweed farming, off-shore system, on-shore system, techno-economic analysis, community participation, Kelantan